Information Theoretical Analysis of Biometric Generated Secret Key Sharing Model - Haroutunian , Mariam E.; Pahlevanyan, Narek S. (Mathematical Problems of Computer Science, 2021)
We investigate the biometric generated secret key sharing system. We consider the generalization of the secret key rate, studied by Ignatenko and Willems [1]: the notion of E-achievable secret key rate is introduced. The lower and upper bounds for the largest E-achievable secret key rate are obtained. When E tends to zero, the limits of our bounds coincide and are equal to the largest achievable secret key rate stated in [1].